MODEL PELATIHAN IPS – SEJARAH BERBASIS PENDIDIKAN MULTIKULTURAL UNTUK GURU SMP - Musadad, Akhmad Arif (Paramita: Historical Studies Journal, 2012)
This research aims: (1) to describe the prior condition of teacher competency in History-Social Studies learning in Junior High School; (2) to describe the training form used for the History-Social Studies teacher of Junior High School currently; (3) to describe the form of multicultural education-based History-Social Studies training requirement; and (4) to develop the multicultural education-based History-Social Studies training model for the teacher of Junior High School in Surakarta. This research and development was taken place in Surakarta city. The subject of research was the History-Social Studies teachers of Junior High School. The result of research showed: (1) the prior condition of Social Studies teacherÃ¢â‚¬â„¢s competency in history learning was still low. It could be seen from the teacherÃ¢â‚¬â„¢s low capability of developing RPP (lesson plan), and low capability of implementing the learning; (2) the training form used currently could not improve the teacher competency optimally; (3) the teacher wanted to improve his/her competency through multicultural education-based History-Social Studies training; and (4) the training model developed encompassed three stages: planning, implementation, andÃ‚Â  training evaluation. Keywords: Training Model, History-Social Studies, Multicultural EducationÃ‚Â  Penelitian ini bertujuan untuk: (1) mendeskripsikan kondisi awal kompetensi guru dalam pembelajaran IPS-SejarahÃ‚Â  di SMP; (2) mendeskripsikan bentuk pelatihan yang dipakai untuk guru IPS-Sejarah SMP sekarang ini; (3) mendeskripsikan bentuk kebutuhan pelatihan IPS-Sejarah berbasis pendidikan multikultural; dan (4) mengembangkan model pelatihan IPS-Sejarah berbasis pendidikan multikultural bagi guru SMP di Surakarta. Penelitian dan pengembangan ini dilaksanakan di Kota Surakarta. Subjek penelitian ini adalah guru IPS (sejarah) di sekolah menengah pertama. Hasil penelitian dapat dikemukakan: (1) kondisi awal kompetensi guru IPS dalam pembelajaran sejarah masih rendah. Hal ini dapat dilihat dari rendahnya kemampuan guru dalam menyusun RPP, dan rendahnya kemampuan dalam melaksanakan pembelajaran; (2) bentuk pelatihan yang dipakai sekarang ini kurang dapat meningkatkan kompetensi guru; (3)Ã‚Â  guru ingin meningkatkan kompetensinya melalui pelatihan IPS-Sejarah berbasis pendidikan multikultural; dan (4) model pelatihan yang Dikembangkan mempunyai tiga tahapan, yaitu: perencanaan, pelaksanaan, dan evaluasi pelatihan Kata Kunci: Model Pelatihan, IPS-Sejarah, Pendidikan Multikultural. Ã‚Â